Additive construction using enhanced earthen-based composites: Improvement of the mechanical strength and water durability using chitosan and agave fibers - (:unkn) unknown (Elsevier BV, 2024)
3D printing has emerged as a revolutionary technology with potential applications in the construction industry. However, the prevalent use of ordinary cement in most 3D printing formulations results in significant greenhouse gas emissions during 3D print...
Keywords: Materiales compuestos; Construcción aditiva